2012
DOI: 10.1016/j.jtcvs.2012.03.035
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal membrane oxygenation after stage 1 palliation for hypoplastic left heart syndrome

Abstract: Mortality for neonates with hypoplastic left heart syndrome supported with ECMO after stage 1 palliation is high. Longer ventilation before cannulation, longer support duration, and ECMO complications increased mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
94
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(108 citation statements)
references
References 8 publications
10
94
4
Order By: Relevance
“…In our series, 13.2% of children required ECMO after the Norwood operation, comparable with the results of the SVR trial (15.5%) [9]. Survival in our patients who required ECMO was 41.4%, which is favorable compared with hospital survival of 31% in a recent Extracorporeal Life Support Organization report that examined the outcomes in 738 neonates who required ECMO after the Norwood operation [24]. Furthermore, several reports showed that the long-term outcomes in hospital survivors who required ECMO support after the Norwood operation is poor [9,[25][26][27].…”
Section: Commentsupporting
confidence: 85%
“…In our series, 13.2% of children required ECMO after the Norwood operation, comparable with the results of the SVR trial (15.5%) [9]. Survival in our patients who required ECMO was 41.4%, which is favorable compared with hospital survival of 31% in a recent Extracorporeal Life Support Organization report that examined the outcomes in 738 neonates who required ECMO after the Norwood operation [24]. Furthermore, several reports showed that the long-term outcomes in hospital survivors who required ECMO support after the Norwood operation is poor [9,[25][26][27].…”
Section: Commentsupporting
confidence: 85%
“…Overall Patterns of ECMO Care: 1989 Overall, 290 ELSO centers provided ECMO support to 56,222 individuals (30,909 neonates, 14,725 children, and 10,588 adults). ECMO mortality rates for neonatal respiratory, cardiac, and ECPR were 26%, 59%, and 59%, respectively, compared with 43%, 49%, and 59% among pediatric patients and 43%, 60%, and 71% among adults.…”
Section: Resultsmentioning
confidence: 99%
“…The following variables were chosen: calendar year in which ECMO was delivered (15,23); patient age (23)(24)(25); primary diagnosis (23)(24)(25)(26)(27); ECMO support type (16,27); presence of pre-ECMO acute renal failure (23,26,27); presence of comorbid conditions (23,28); pre-ECMO cardiac arrest (25,29); and pre-ECMO measures including duration of mechanical ventilation (23,25,30), arterial blood pH (23,27,31), Pa CO 2 (25), and the ratio of arterial partial pressure of oxygen to fraction of inspired oxygen (PF ratio) (1,23). In neonatal patients, case-mix was also adjusted for gestational age (24) and birth weight (24).…”
Section: Selection Of Variables and Risk Adjustmentmentioning
confidence: 99%
“…After stage I palliation, the rate of poor clinical outcomes is high, with survival estimates ranging from 31% to 38% in patients requiring ECMO and 37% in patients who had cardiac arrest requiring CPR. [22][23][24] The impact of adverse events on ventricular function is less defined. Our data revealed that there was an association between adverse events and ventricular dysfunction, with higher rates of transient and persistent dysfunction present in patients with adverse events after both stage I and stage II palliation.…”
Section: Impact Of Adverse Events On Ventricular Dysfunction and Survmentioning
confidence: 99%